Морфологическая изменчивость и систематический статус трематоды Dicrocoelium petrowi (Digenea, Dicrocoeliidae) - Король, Э.Н. (Збірник праць Зоологічного музею, 2014)
Трематоды от кеклика (Alectoris chukar) из коллекции отдела паразитологии Института зоологии им. И. И. Шмальгаузена НАН Украины были определены нами как Dicrocoelium petrowi Kassimov, 1952 (Digenea, Dicrocoeliidae). В статье приведены описание половозрелых трематод и их морфологическая изменчивость. Вид регистрируется впервые на территории Украины (Крым). Трематоди від кеклика (Alectoris chukar) з колекції відділу паразитології Інституту зоології ім. І. І. Шмальгаузена НАН України були визначені нами як Dicrocoelium petrowi Kassimov, 1952 (Digenea, Dicrocoeliidae). У статті наведено опис статевозрілих трематод і їх морфологічна мінливість. Вид реєструється вперше на території України (Крим). Trematodes retained in the collection (Department of Parasitology, Schmalhausen Institute of Zoology NAS Ukraine) learned from chukar partridge (Alectoris chukar) were identified as Dicrocoelium petrowi Kassimov, 1952 by its morphological features. Description of adult trematodes and their morphological variability were given. This species was recorded for the first time for Ukraine (Crimea).